2020
DOI: 10.1159/000513641
|View full text |Cite
|
Sign up to set email alerts
|

First Record of a B Chromosome in <b><i>Polybia fastidiosuscula</i></b> Saussure (Vespidae) and Investigation of Chromatin Composition Through Microsatellite Mapping

Abstract: The characterization of karyotypes is an important aspect in understanding the structure and evolution of genomes. Polybia is a genus of social wasps of the family Vespidae. This genus has 58 species, but for only 8 of these chromosome number and morphology have been reported in the literature. The aim of this study was to describe and characterize the Polybia fastidiosuscula Saussure karyotype, presenting the first case of a B chromosome in Vespidae. In addition, we investigated the chromatin composition of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 53 publications
2
5
0
Order By: Relevance
“…The distribution pattern of microsatellite (GA) 15 observed on the chromosomes of C. rimosus was restricted to the euchromatic region, corresponding to most of the chromosomal length, a pattern similar to that reported for C. transversus (2n = 18), other fungus-farming ants [Micolino et al, 2019b;Teixeira et al, 2022], and other hymenopterans [Travenzoli et al, 2019;Marchioro et al, 2020]. In contrast to C. rimosus, which showed a scattered distribution pattern for microsatellite (GA) 15 , additional specific bands have been observed in other fungus-farming ants, such as Mycetomoellerius holmgreni (Wheeler, 1925) [Micolino et al, 2019b], Sericomyrmex sp., and Mycocepurus goeldii (Forel, 1893); these bands may be related to mobile elements or gene regions [Teixeira et al, 2022].…”
Section: Discussionsupporting
confidence: 78%
“…The distribution pattern of microsatellite (GA) 15 observed on the chromosomes of C. rimosus was restricted to the euchromatic region, corresponding to most of the chromosomal length, a pattern similar to that reported for C. transversus (2n = 18), other fungus-farming ants [Micolino et al, 2019b;Teixeira et al, 2022], and other hymenopterans [Travenzoli et al, 2019;Marchioro et al, 2020]. In contrast to C. rimosus, which showed a scattered distribution pattern for microsatellite (GA) 15 , additional specific bands have been observed in other fungus-farming ants, such as Mycetomoellerius holmgreni (Wheeler, 1925) [Micolino et al, 2019b], Sericomyrmex sp., and Mycocepurus goeldii (Forel, 1893); these bands may be related to mobile elements or gene regions [Teixeira et al, 2022].…”
Section: Discussionsupporting
confidence: 78%
“…tif, the canonical telomeric sequence in vertebrates, have been previously observed in some chromosomes of bulldog ants through FISH (Meyne et al 1995) and even in the fire ant Solenopsis invicta Buren, 1972 (Myrmicinae) through sequencing analysis (Wurm et al 2011). The (TCAGG) n motif has been detected in telomeres of some clades of the order Coleoptera (reviewed by Kuznetsova et al 2020) and has recently been characterized as a microsatellite located in the centromeric heterochromatin of the social wasp P. fastidiosuscula (Marchioro et al 2020). Our physical mapping data showed that such telomeric sequence variations are absent in any portion of the A. cephalotes chromosomes.…”
Section: Discussionmentioning
confidence: 97%
“…In the present study, the heterochromatin of A. cephalotes had no trace of several microsatellites, such as (GA) 15 , (CA) 15 , (TAT) 10 , (CGG) 10 , (GAG) 10 , (CAA) 10 , and (TCAGG) 6 . However, these microsatellites are present in the heterochromatic regions of other Hymenoptera species, like the bees' Frieseomelitta species and M. seminigra merrilae, and the wasp P. fastidiosuscula (Santos et al 2018;Marchioro et al 2020;Barbosa et al 2021). Either these microsatellites were located in euchromatin, or there were no signals produced on the A. cephalotes chromosomes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations